Analisis Rancang Bangun Pembangkit Listrik Dengan Mesin Sepeda Motor Dengan Penggerak Mula Terkendali (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Utilization of DC motors for moving the mechanical drive in place of the gas starter (prime mover). Which controlled by a controller to regulate the movement of the voltage controlled DC motor power window. Change of generator output voltage will read the sensor voltage Vout generator converted to a voltage which in this Vdc. Voltage read ATMEGA8 Mickrokontroler IC by using the ADC will determine the movement of the motor as the controller of gas, if the voltage is less than 220 V to its minimum voltage of the motor which has coupled on gas prime movers will rotate clockwise so the motor is pulling gas to reach the expected speed of the generator and its reverse in case of overspeed which causes more stress then the generator will rotate anti-clockwise so that the gas will drop to adjust the speed generator. So, rotation of DC motors forward and reverse and at a predetermined voltage level is normal voltage 220 -230 V motor will stop, and will hold the gas engine driving the generator speed will be maintained so long as the voltage under normal conditions 220-230 V. . Keywords: DC Motor, DC Motor Driver, microkontroller ATMEGA8, Vdc Power Supply.